Análisis de la sincronización de celo con benzoato de estradiol y progesterona en hembras bovinas para carnes - Villota Ruiz, Kevin Joel (2022)
The purpose of this bibliographic work was to analyze the estrus synchronization methods with the use of estradiol benzoate and progesterone in beef cattle. The qualitative and exploratory method was used in databases published in indexed journals, scientific articles and web pages. Ecuador has a cattle herd of 4.5 million head of cattle of different breeds. the majority of heads corresponded to females older than 2 years (42%), followed by bulls between 1 and 2 years old (28%). The largest production of beef cattle is located in the provinces of Manabí, Esmeralda, Santo Domingo de los Tsáchilas and Guayas. The evaluation of the body condition must be carried out at weaning, 90 days before the calving of the cow and at the breeding season. In the bovine genetic improvement plan, developed by the Ministry of Agriculture, Livestock, Aquaculture and Fisheries of the province of Oro, year 2015, heat synchronizers (CIDR intravaginal device), prostaglandin and estradiol benzoate were used. 440 cows were inseminated at a fixed time, of which 198 became pregnant with 45% gestation. The synchronization of heat or estrus, using estradiol benzoate and progesterone in cattle for meat in artificial insemination programs, conception percentages of 51% and pregnancy rates of 60 and 70% are obtained. synchronization protocols with Co-Synch intravaginal devices, higher pregnancy rates (42%) are obtained. With estradiol cypionate, pregnancy rates are lower (39%). Estrus presentation in cows with estradiol is higher (95%) in relation to Co-Synch (85%).